Transcriptional Changes after Enniatins A, A1, B and B1 Ingestion in Rat Stomach, Liver, Kidney and Lower Intestine - Alessandra Cimbalo; Manuel Alonso-Garrido; Guillermina Font; Massimo Frangiamone; Lara Manyes (Foods, 2021)
Enniatins (ENs) are depsipeptide mycotoxins produced by Fusarium fungi. They are known for their capacity to modulate cell membrane permeability and disruption of ionic gradients, affecting cell homeostasis and initiating oxidative stress mechanisms. The effect of the acute toxicity of ENs A, A1, B and B1 at two different concentrations after 8 h of exposure was analysed in Wistar rats by a transcriptional approach. The following key mitochondrial and nuclear codified genes related to the electron transport chain were considered for gene expression analysis in stomach, liver, kidney and lower intestine by quantitative Real-Time PCR: mitochondrially encoded NADH dehydrogenase 1 (MT-ND1), mitochondrially encoded cytochrome c oxidase 1 (MT-COX1), succinate dehydrogenase flavoprotein subunit A and ATP synthase F1 subunit alpha, respectively. Moreover, the expression of markers involved in oxidative stresssuperoxide dismutase 1 (SOD1), glutathione peroxidase 1 (Gpx1), heme oxygenase 1, apoptosis B-cell lymphoma 2, Bcl2 Associated protein X (Bax), tumor suppressor protein (p53), inhibition of apoptosis nuclear factor kappa of activated B cells, immune system interleukin 1β and intestinal tight junction Occludin merely in lower intestine tissues have been investigated. For mitochondrial genes, the main differences were observed for MT-ND1 and MT-COX1, showing its deficiency in all selected organs. With regard to the intestinal barrier’s cellular response to oxidative stress, the activity of the antioxidant gene SOD1 was decreased in a dose-dependent manner. Similarly, the catalytic enzyme GPx1 was also downregulated though merely at medium dose employed. On the contrary, the pro-apoptotic Bax and p53 regulators were activated after ENs exposure, reporting a significant increase in their expression. Furthermore, the alteration of intestinal permeability was assessed by the abnormal activity of the tight junction protein occludin. In summary, ENs may generate mitochondrial disorders and induce oxidative stress in intestinal barrier function.